2017
DOI: 10.1093/icvts/ivx394
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and timing of surgery in the left-sided infective endocarditis: an Italian multicentre study

Abstract: Our study did not confirm a better overall survival in patients undergoing early surgery. However, even with the use of statistical techniques to control biases, we could not draw definitive conclusions that early surgery is not beneficial. Our results need to be assessed by randomized trials before any changes in clinical practice can be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
4
7
0
Order By: Relevance
“…The main IE agent was S. aureus (21.9%), followed by viridans streptococci (17.7%), enterococci (13.3%), bovis -group streptococci (11.0%) and coagulase-negative staphylococci (10.9%). Similar distributions of causative microorganisms were reported in other Italian studies [32] , [33] , [34] , [36] , [37] . Other characteristics of IE in Italy include an elevated ratio of healthcare-associated cases (12.4–64.6% of cases) and a low rate of zoonotic and arthropod-borne microorganisms, notably C. burnetii and Bartonella spp.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The main IE agent was S. aureus (21.9%), followed by viridans streptococci (17.7%), enterococci (13.3%), bovis -group streptococci (11.0%) and coagulase-negative staphylococci (10.9%). Similar distributions of causative microorganisms were reported in other Italian studies [32] , [33] , [34] , [36] , [37] . Other characteristics of IE in Italy include an elevated ratio of healthcare-associated cases (12.4–64.6% of cases) and a low rate of zoonotic and arthropod-borne microorganisms, notably C. burnetii and Bartonella spp.…”
Section: Resultssupporting
confidence: 88%
“…In Italy, the incidence rate of IE is 4.6/100 000 person-years, with a higher rate in people older than 65 years (11.7/100 000 person-years) [32] . Several studies demonstrated temporal changes in IE epidemiology, similar to those observed in other European countries [32] , [33] , [34] , [35] , [36] , [37] : an increase in patient age (57 to 69 years old, depending on the series), rate of prosthetic heart valve and comorbidity factors such as diabetes mellitus, chronic renal failure and cancer [33] . In the largest series, Leone et al .…”
Section: Resultssupporting
confidence: 64%
“…In our study, we found that the mean age at the time of IE episodes were younger than those reported from developed countries, although the mean age increased during this period. The proportion of old patients with IE increased gradually in our study period, and this shown the same trend as the developed countries [7,9].Erichsen et al [10] found that the incidence increased substantially for elderly patients between 1994 and 2011, with the highest incidence rate of 3.38 for patients more than 80 years old at IE onset. In Oliver et al' s report [11], 49% of IE patients were over 65 years old and 11.2% were over 80 years old.…”
Section: Discussionsupporting
confidence: 80%
“…In a recent meta‐analysis, patients operated for left‐sided endocarditis within 7 days after diagnosis had better survival in comparison to patients operated later or managed medically . However, in some retrospective studies, the benefit of ES has been questioned . In our study, even though patients operated within 7 days of prior directed antimicrobial treatment had a higher frequency of acute heart failure and emergency surgery, their 30‐day and late mortality were compared with patients operated later.…”
Section: Discussionsupporting
confidence: 61%
“…12 However, in some retrospective studies, the benefit of ES has been questioned. 13,14 In our study, even though patients operated within 7 days of prior directed antimicrobial treatment had a higher frequency of acute heart failure and emergency surgery, their 30-day and late mortality were compared with patients operated later. In the randomized Early Surgery versus Conventional Treatment for Infective endocarditis (EASE) study, surgery within 48 hours for IE was shown to decrease the composite endpoint of death from any cause and embolic events.…”
Section: Discussionmentioning
confidence: 72%